The Importance of Educational Technologies in Students' Acceptance and Mastery Of The Subject (Texas Journal of Multidisciplinary Studies, 2024)
By applying pedagogical technology methods in modern lessons, additional information (handouts, tests, problems, riddles, questions and answers, various crosswords, experiments, etc.) should cover the main topic during the lesson. At the end of the lesson, the students will have sufficient knowledge about the scientific information, the place in the field of science and technology development, as well as the encyclopedic scientists who lived in the past. they should also have information about their contributions to the development of this field. For this, it is necessary to use methods of pedagogical technology that are appropriate and convenient for the subject being taught in each lesson. In the implementation of this activity, high pedagogical skills are required from the teacher.